MODERN APPLICATIONS OF PROFIT-SALE (BAYʿ MURĀBAḤAH) FROM A MAQĀṢID SHARĪʿAH PERSPECTIVE - Mohammed Farid Ali al-Fijawi; Saidatolakma Mohd Yunus, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2019)
This paper looks into profit-sale (murābaḥah), a nominal sale contract in Islam, in search for Sharīʿah objectives embedded in the corpus according to the terms and conditions of the contract. In light of these objectives, applications of the profit-sale contract as afinancing tool by Islamic Finance Institutions (IFIs) are examined.The study discovers that some modern applications bypass theprimary Sharīʿah objectives of a sale contract, such as the sellertaking liability for possible risks and having real possession of theitems on sale. Contrary to this, the seller transfers his liability to thecustomer and takes possession (qabḍ) of the goods on paper onlyinstead of possession in the real sense. Such applications distort themode of trading real goods into a mere disguise for an increase incredit or riba.